2010
DOI: 10.13073/0015-7473-60.3.226
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Standards for Harvesters and Processors in Italy

Abstract: The authors developed a general productivity model for the harvesters and processors currently used in Italy. The model consists of a set of mathematical relationships that can estimate the productivity of these machines under the whole range of specific work conditions faced in Italy. Such relationships can provide general directions to prospective users and can contribute to the development of scenario predictions. The original data pool contained more than 15,000 individual timestudy records, each represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Given the limited detail included in a long-term study, it is difficult to thoroughly discuss the similarities and the differences between the figures obtained from this study and those reported in the general literature on the subject. However, the figures in this study are generally compatible with those indicated in the literature, and they match quite well the Italian productivity standards for harvesters and processors [26]. This said, readers must be aware that direct comparison can be deceiving, because most of the existing productivity figures are obtained from short-term time study sessions, not from long-term company records.…”
Section: Discussionsupporting
confidence: 87%
“…Given the limited detail included in a long-term study, it is difficult to thoroughly discuss the similarities and the differences between the figures obtained from this study and those reported in the general literature on the subject. However, the figures in this study are generally compatible with those indicated in the literature, and they match quite well the Italian productivity standards for harvesters and processors [26]. This said, readers must be aware that direct comparison can be deceiving, because most of the existing productivity figures are obtained from short-term time study sessions, not from long-term company records.…”
Section: Discussionsupporting
confidence: 87%
“…For example, the clear-cutting data in the study by Nurminen et al [76] included 636 stems, and the data in the study by Dvořák [30] included 631 processed trees. There are some other larger sets of cutting data of clear cuts but they are mainly long-term follow-up studies, such as the study by Spinelli et al [77] in which the data included 15,366 trees. Further examples include the research by Gerasimov et al [78] in which 4.3 million stems were cut, and the research by Eriksson and Lindroos [62] which had a dataset of more than 12,000 clear-cut stands.…”
Section: Evaluation Of Datasets and Approachesmentioning
confidence: 99%
“…Due to a large area of forestland with small diameter trees [13], the diameter range of interest in Maine and this region is from 10 cm to 33 cm. The majority of the reviewed studies fall within the dbh range of interest, however, only few cover the entire diameter range [3,23,29]. Stem size also affects skidding and forwarding productivity.…”
Section: Stem Sizementioning
confidence: 99%
“…Spinelli et al [3] reported that in addition to significantly limiting accessibility of a stand, slope affects the moving time within the stand. A wide range of slopes have been studied previously, ranging from level ground to slopes of 45% (Figure 4).…”
Section: Slopementioning
confidence: 99%
See 1 more Smart Citation